Long-term couple relationships - stress, problems and coping processes in couple counseling: Insights based on five case studies with five long-term couples - Kieslich, Ute; Steins, Gisela (Frontiers in Psychology, 2022)
In the course of demographic change, the proportion of older people in many countries is rising and the need for couple counselling in old age is growing in parallel with demographic developments. However, empirical studies on couple therapy with older people in long-term couple relationships exist to date only to a limited extent. The focus of our research is predominantly on the self-regulatory abilities of individuals with regard to various stresses as well as dyadic processes in the shaping of long- term couple relationships in old age. The research is explorative in character, focuses on the content of the couple relationship and consistently focuses on the subjective perspective of people aged 55 and older who live in long-term couple relationships and have received couple counselling. The structuring aspects of the study are the stress factors, problem areas and coping processes of the study’s participants. The aim is to be able to describe details of these factors. 5 couples from a standardized questionnaire study concerning the individual and couple-related stress factors and problems at the beginning (N=62) and the end (N=36) of their couple counselling process were the interviewees for the following interview study, dentral in this contribution. The results serve as a suggestion for further research and can only be interpreted with caution due to the small sample: The central results of the interview study are summarized in a circular process model and are discussed in the light of relevant theoretical approaches. The most important results are: To prevent negative emotions and destructive conflicts with their spouse, some of the interviewed partners actively used avoidance strategies in couple interactions. Upon completion of couple therapy changes in the couple relationships appeared instable as soon as overcharging stress factors occurred again. The results suggest that an approach to couple therapy for older people in long-term couple relationships should prioritize emotional safeness and attachment in couple relationship to facilitate constructive conflict management. The couple therapy process should emphasize emotion regulation strategies based on age-related strengths and consider age-related vulnerabilities. Moreover, long-term couples may benefit from catamnestic consultation appointments to consolidate the developed changes.